2022
DOI: 10.2147/ijgm.s341072
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Associated Acute Kidney Injury: Advances and Challenges

Abstract: A decrease in renal function that follows intravascular administration of contrast medium (CM) within a few days is reported as contrast-induced acute kidney injury (CI-AKI). In clinical practice, the imaging procedure is frequently deferred when clinicians consider that the renal risks caused by CM outweigh the benefits of enhanced imaging. However, with an in-depth understanding of AKI and contrast medium, scholars have realized that the decrease in renal function after CM is caused by contrast medium factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…21 In addition, according to the available studies, contrast medium (CM) caused less damage in patients with normal renal function. 22 Therefore, for patients with normal renal function, even if CA-AKI occurs, its effect on renal function was negligible. And, according to Supplementary FIGURE2 , we found that the occurrence of PKI did not make a large difference in patient survival for the STAGE I group.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, according to the available studies, contrast medium (CM) caused less damage in patients with normal renal function. 22 Therefore, for patients with normal renal function, even if CA-AKI occurs, its effect on renal function was negligible. And, according to Supplementary FIGURE2 , we found that the occurrence of PKI did not make a large difference in patient survival for the STAGE I group.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI study protocol consists of 3D-T1, axial T2, 3D-FLAIR, DWI and SWI sequences. All patients will be evaluated for renal function status before undergoing brain imaging to reduce the risk of contrast-induced nephropathy [ 53 ]…”
Section: Methodsmentioning
confidence: 99%
“…The MRI study protocol consists of 3D-T1, axial T2, 3D-FLAIR, DWI and SWI sequences. All patients will be evaluated for renal function status before undergoing brain imaging to reduce the risk of contrast-induced nephropathy (51)…”
Section: Methodsmentioning
confidence: 99%
“…The MRI study protocol consists of 3D-T1, axial T2, 3D-FLAIR, DWI and SWI sequences. All patients will be evaluated for renal function status before undergoing brain imaging to reduce the risk of contrast-induced nephropathy (51) The stroke volume (hematoma/infarct volume) is calculated using the ellipsoid method A+B+C/2, where A represents the largest diameter, B represents the largest diameter perpendicular to A, and C represents the product of slice thickness and number of slices. A, B, and C are measured in centimetres, and the resulting volume are expressed in cm3 or milliliters (8,52) Leukoaraiosis are defined as bilateral areas of patchy or diffuse hypodensity on CT or white matter hyperintensity on MRI (Yang et al, 2015).…”
Section: Electrocardiogrammentioning
confidence: 99%